What induces watts in WAT?. (2nd April 2016) - Forest, Claude; Joffin, Nolwenn; Jaubert, Anne-Marie; Noirez, Philippe
ABSTRACT: Excess calories stored in white adipose tissue (WAT) could be reduced either through the activation of brown adipose tissue (BAT) or the development of brown-like cells ("beige" or "brite") in WAT, a process named "browning." Calorie dissipation in brown and beige adipocytes might rely on the induction of uncoupling protein 1 (UCP1), which is absent in white fat cells. Any increase in UCP1 is commonly considered as the trademark of energy expenditure. The intracellular events involved in the recruitment process of beige precursors were extensively studied lately, as were the effectors, hormones, cytokines, nutrients and drugs able to modulate the route of browning and theoretically affect fat mass in rodents and in humans. The aim of this review is to update the characterization of the extracellular effectors that induce UCP1 in WAT and potentially provoke calorie dissipation. The potential influence of metabolic cycling in energy expenditure is also questioned.